Art of Using Language in Sukhothai Local Literature: Phra Ruang Phra Lue Legendary Sukhothai Heroes by Mr. Kiang Chamni - Khemmongkhonsiri, Chusak; Khunmathurot, Songphop; Ngourangsri, Chayatee (Ratchaphruek Journal, 2024)
The research article on the art of language use in Sukhothai local literature, titled "Phra Ruang Phra Lue, the Legendary Sukhothai Hero" by Mr. Kiang Chamni, aims to study and analyze the art of language use in this specific literary work. The research tool was the book "Phra Ruang Phra Lue, the Legendary Sukhothai Hero." The results of the research found that the local Sukhothai literature by Mr. Kiang Chamni demonstrates the art of language use, which can be classified into 10 types: the use of the Sukhothai dialect, repeated words, double words, colloquial words, foreign language words, simile, personification, hyperbole, and axioms. The unique highlight is the appropriate and interesting use of the Sukhothai language, showing that this literature has the art of language that creates enjoyment in reading. It is the provincial language of Sukhothai, which is easy to read and understand. The literature also includes insights that can be applied in everyday life, particularly in speech and communication. All of these language features create an image that is consistent with the essence of the story.